2011
DOI: 10.1161/hypertensionaha.111.178178
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Diastolic Hypotension and Incident Heart Failure in Older Adults

Abstract: Aging is often associated with increased systolic blood pressure and decreased diastolic blood pressure. Isolated systolic hypertension or an elevated systolic blood pressure without an elevated diastolic blood pressure is a known risk factor for incident heart failure in older adults. In the current study, we examined whether isolated diastolic hypotension, defined as a diastolic blood pressure <60 mm Hg and a systolic blood pressure ≥100 mm Hg, is associated with incident heart failure. Of the 5795 Medicare-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…The findings of this study by Guichard et al 17 should be interpreted within the context of its limitations. The definition of isolated diastolic hypotension can be questioned.…”
Section: Bp and Heart Failure Risk Assessmentmentioning
confidence: 55%
See 2 more Smart Citations
“…The findings of this study by Guichard et al 17 should be interpreted within the context of its limitations. The definition of isolated diastolic hypotension can be questioned.…”
Section: Bp and Heart Failure Risk Assessmentmentioning
confidence: 55%
“…17 Using the community-dwelling Cardiovascular Health Study population that was free of centrally adjudicated heart failure at baseline, Guichard et al 17 identified isolated diastolic hypotension (defined as DBP <60 mm Hg with SBP ≥100 mm Hg) as a new biomarker of incident heart failure. They identified 5376 subjects free of heart failure, of whom 751 (14%) fit the diagnosis of isolated diastolic hypotension.…”
Section: Bp and Heart Failure Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…23, 24 The effectiveness of propensity score model was assessed by estimating absolute standardized differences, and results were presented as a Love plot (Figure 1). 2527 Absolute standardized differences values <10% are considered inconsequential and 0% indicates no residual bias.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were divided into five groups based on SBP High NT-proBNP** 1,790 (27) Unless indicated otherwise, data are given as the mean ± SD, n (%), or as the median [interquartile range]. *Hypertension was defined as being on antihypertensive medications and/or SBP ≥140 mmHg and/or DBP ≥90 mmHg.…”
Section: Participant Classificationmentioning
confidence: 99%